Influence Of Fertilizers on African Procorry Growing (ННВВС) - Jamoliddin, Eshonkulov; Akhmad, Abdumajitov; Laylo, Isoyeva (American Journal of Botany and Bioengineering, 2025)
The article presents the results of studying the influence of mineral, organic, and micro-fertilizers on the growth, development, and yield of African millet. Their physiological functions, influence on root system formation, photosynthetic activity, grain filling, and yield quality are examined. It has been shown that the optimal nutrition system includes the combination of mineral fertilizers with organic fertilizers, which ensures maximum crop productivity in arid climates and irrigated agriculture.